2010
DOI: 10.1098/rspb.2010.1639
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable morphological stasis in an extant vertebrate despite tens of millions of years of divergence

Abstract: The relationship between genotypic and phenotypic divergence over evolutionary time varies widely, and cases of rapid phenotypic differentiation despite genetic similarity have attracted much attention. Here, we report an extreme case of the reverse pattern-morphological stasis in a tropical fish despite massive genetic divergence. We studied the enigmatic African freshwater butterfly fish (Pantodon buchholzi), whose distinctive morphology earns it recognition as a monotypic family. We sequenced the mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 18 publications
4
59
0
Order By: Relevance
“…However, Hilton (2003) found that Mormyridae is a sister-group of Notopteridae + Osteoglossidae, and Kumazawa and Nishida (2000) used the mtDNA cytb gene sequence to demonstrate that Osteoglossidae + Mormyridae is a sister-group to Notopteridae. Our analysis showed that the family Osteoglossidae is a sister-group to Notopteridae + Mormyridae + Gymnarchidae, that Notopteridae is a sister-group to Mormyridae + Gymnarchidae and that Mormyridae is a sister-group to Gymnarchidae, which is in agreement with the recent studies mentioned above (Lavoué et al 2004(Lavoué et al , 2011Inoue et al 2009). …”
Section: Phylogenetic Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…However, Hilton (2003) found that Mormyridae is a sister-group of Notopteridae + Osteoglossidae, and Kumazawa and Nishida (2000) used the mtDNA cytb gene sequence to demonstrate that Osteoglossidae + Mormyridae is a sister-group to Notopteridae. Our analysis showed that the family Osteoglossidae is a sister-group to Notopteridae + Mormyridae + Gymnarchidae, that Notopteridae is a sister-group to Mormyridae + Gymnarchidae and that Mormyridae is a sister-group to Gymnarchidae, which is in agreement with the recent studies mentioned above (Lavoué et al 2004(Lavoué et al , 2011Inoue et al 2009). …”
Section: Phylogenetic Analysissupporting
confidence: 93%
“…Currently, most of these species live in freshwater and are intolerant of saltwater. According to previous studies, the close phylogenetic relationships among these four genera have been recognized at both the morphological (Hiton 2003;Nelson 2006) and molecular levels (Kumazawa & Nishida 2000;Lavoué et al 2004Lavoué et al , 2011Yue et al 2006;Inoue et al 2009;Mu et al 2012). Furthermore, our results are in good agreement with the commonly accepted phylogenetic consensus, which places A. gigas (Arapaima) and H. niloticus (Heterotis) as a sister-group and the Scleropages species as a sister clade to the two species of Osteoglossum.…”
Section: Phylogenetic Analysissupporting
confidence: 91%
“…Although the isolated distribution of Anelytropsis in Mexico makes deep divergence from other dibamids intuitively reasonable, the even deeper split between two geographically adjacent and nonoverlapping Dibamus clades was quite unexpected. Such an ancient divergence between morphologically similar congeners (no morphological characters diagnose these clades; [20]) provides a striking example of morphological stasis, one apparently predating other recently documented cases [46][47][48]. Further taxon sampling is necessary to know the full extent of geographical concordance within clades, but our results (along with the substantial number of coastal island endemics and very restricted mainland ranges; see the electronic supplementary material) thus suggest a remarkably low propensity for even relatively local dispersal throughout the Tertiary.…”
Section: Discussionmentioning
confidence: 99%
“…Testing whether changes in Scn4aa expression coincided with two independent origins of adult EO myo requires a robust phylogeny on which to infer the timing of these events. Although a sound knowledge of mormyroid phylogeny has been acquired using genetic data (9,22,27,28), the overall gymnotiform phylogeny has remained less resolved (14,19,29,30). Thus, we inferred phylogenetic relationships among the teleosts that we investigated using four datasets: all nucleotide positions of both paralogs concatenated ("Concat"), all positions of each gene separately, and only third-codon positions of the concatenated data set ("Concat3rd").…”
Section: Changes In Paralog Expression In Electric Fish Relative To Omentioning
confidence: 99%
“…More than 100 million years after the WGD, gymnotiform and mormyroid electric fishes arose independently from nonelectrogenic ancestors (17,(19)(20)(21)(22). Due to the WGD, nonelectrogenic teleosts possess two Scn4a paralogs that are expressed in SM (23, 24).…”
mentioning
confidence: 99%